White awake : an honest look at what it means to be white - Hill, Daniel, 1973- (InterVarsity Press, 2017)
"Daniel Hill will never forget the day he heard these words: 'Daniel, you may be white, but don't let that lull you into thinking you have no culture. White culture is very real. In fact, when white culture comes in contact with other cultures, it almost always wins. So it would be a really good idea for you to learn about your culture.' Confused and unsettled by this encounter, Hill began a journey of understanding his own white identity. Today he is an active participant in addressing and confronting racial and systemic injustices. And in this compelling and timely book, he shows you the seven stages to expect on your own path to cultural awakening. It's crucial to understand both personal and social realities in the areas of race, culture, and identity. This book will give you a new perspective on being white and also empower you to be an agent of reconciliation in our increasingly diverse and divided world"--Back cover.